Can black coral forests be detected using multibeam echosounder “multi-detect” data? - Feldens, Peter; Held, Philipp; Otero-Ferrer, Francisco; Bramanti, Lorenzo; Espino, Fernando; Schneider von Deimling, Jens (Frontiers in Remote Sensing, 2023)
The black coral Anthipatella wollastoni (Gray, 1857) builds marine animal forests in the mesophotic zone. The spatial extension of the black coral forests is not well known in many regions. Due to a skeleton composed of protein and chitin, the coral is difficult to image by acoustic remote sensing methods when compared to corals forming carbonate skeletons. Manufacturers recently introduced a novel data type, so-called “multi-detections” to their sonars that provides additional target detections per beam, besides the primary bottom detection. In this study, we utilized a Norbit chirp multibeam echo sounder in multidetect mode to record up to three targets in each beam in an area with black coral occurrence below 45 m depth, situated offshore Lanzarote (Canary Islands, Spain). Multi-detections allow to identify features above and below the seafloor, without the need to store and process full water column information. A comparison of multi-detect soundings with ground truthing by technical divers and underwater cameras shows that black corals can be detected. However, repeatability of the detections is limited, and further sensitivity studies are required.